Desain Komunikasi Visual untuk Menunjang Kampanye Kesadaran Buang Sampah pada Tempatnya dan Pemanfaatan Sampah - Latifah, Isanilda Dea (Humaniora, 2011)
Public awareness will live in a clean environment within their important behavior of throwing garbage into a garbage can and also managing garbage so it could raise other benefits in environment conservation. As a visual communication designer, we must care about everything we do to get the result of public purpose that care with environment cleanliness and conservation. Therefore, it is hoped that will be easier for us to design the good concept to create social design regarding our efforts to remind how importance of public awareness towards cleanliness and the behavior of throwing garbage into the garbage can and manage garbage into beneficial products.